Isolation and expansion of cardiosphere-derived stem cells - Tan, J; Carr, C; Stuckey, D; Ellison, G; Messina, E; Giacomello, A; Clarke, K (2011)
The isolation and in vitro expansion of stem cells from the adult heart may provide a cell therapy for regenerating damaged myocardium. Cardiac stem cells can be isolated via magnetic or fluorescent cell sorting using specific cell-surface markers, including c-kit, Sca-1, and Isl-1. Because these isolation methods yield relatively few cells, substantial in vitro expansion is required to generate sufficient cell numbers for therapy. An alternative method uses cells spontaneously shed from cultured heart explants, which are harvested, induced to form cardiospheres, and expanded as a monolayer for several passages. This method for generating therapeutically relevant numbers of cells in a shorter time period than cell surface marker-based isolations is ideally suited for autologous cardiac stem cell therapy after myocardial infarction. © 2011 by John Wiley and Sons, Inc.